BÖBREK TRANSPLANTASYONLU HASTALARDA GASTROİNTESTİNAL SİSTEME AİT KOMPLİKASYONLAR - İLKOVA, Feryal; GÜRSU, Rıza; GÜNTÜRK, Arzu; DOBRUCALI, Ahmet; BAL, Kadir; TUNCER, M. Murat; OKTAY, Ergun (Cerrahpaşa Medical Journal, 2019)
Background and Design.. Gastrointestinal complications are very important in morbidity and mortality of renal transplant receivers in developed countries. In our study we retrospectively examined 140 patients (103 male and 37 female) who had renal transplantation from 1985 to 1999 in Cerrahpaşa Medical Faculty, Internal Medicine Department, Transplantation section. Results.- There were 15 patients who smoked cigarette continuously (10.71%). None of the patients had a story of alcohol using and 4 of them (2.85%) used analgesic drugs regularly. Story of gastrointestinal disturbances were found in 23 patients (16.42 %) before transplantation. Stomachache (14 patients) was the most seen disturbances in these patients (60.86%). During the preparation period for the transplantation; gastrointestinal endoscopy was made to 71 patients (50.71%), 22 of them (30.98%) was found to be normal. Pathologies found in 49 (69.01%) patients were; gastroduodenitis (12, 24.48%), duodenal ulcer (9, 18.36%), gastritis (8, 16.32%) antral gastritis (6, 12.24%) duodenitis (5, 10.20%), gastrooesaphageal reflux and peptic ulcer (4 each, 8.16%). In 38 of 56 (67.85%) patients who had no complaints before transplantation, pathologies were found by endoscopic examination. Prophylactic medical treatment were given to 72 patients (51.42%) before transplantation. The most used drugs were H2 receptor antagonists. Conclusion.- In our study we found that there is no relationship between gastrointestinal complaints and smoking, alcohol drinking and analgesic using in chronic renal patients who were preparing for transplantation. To find gastrointestinal pathologies; endoscopic examination must be performed to every patient whether they have complaints or not and the pathology must be cured before the transplantation in order to prevent post transplant complications.